P103 The urge to cough in copd. (15th November 2017) - Solomon, A; Cho, PS P; Fletcher, H; Patel, IS; Jolley, CJ; Turner, RD; Birring, SS
Abstract : Introduction: Urge to cough is a conscious perception of the need to cough. We investigated urge-to-cough, triggers and somatic sensations associated with cough in patients with COPD and compared it to patients with chronic refractory cough (CRC). Methods: We undertook a prospective case-control study of COPD patients with chronic cough (≥8 weeks) and patients with CRC. All patients completed a 27-item structured questionnaire (Cough Hypersensitivity Questionnaire; CHQ), that has a 5-point Likert response scale to assess urge-to-cough, aggravating factors/triggers and somatic sensations (0–4; 0=never and 4=occurs all the time in relation to cough). 10 COPD patients underwent a capsaicin challenge test to provoke an urge-to-cough sensation and to assess cough reflex sensitivity. The concentration of capsaicin that elicited 2 or more coughs (C2) and 5 or more coughs (C5) was recorded. Results: 62 COPD and 40 CRC patients were recruited (mean(SD) age 64(11) vs 54(14) years, 48% vs 70% females, FEV1 % predicted 48.2% (19.0) vs 94.1% (16.6) respectively). The top 5 cough triggers and somatic sensations in patients with COPD and CRC are summarised in Table 1 . The severity of sputum trigger of cough and chest sensation associated with cough were significantly greater in COPD compared to CRC; median(IQR) sputum scores: 3 (2–4) vs 2 (1–2) and chest sensation scores: 2 (2–4) vs 1 (0–2) respectively, both p<0.01. The prevalence of urge-to-cough was higher in CRC vs COPD: 97.5% vs 75.8% respectively. The severity of urge to cough and eating/drinking trigger of cough were significantly greater in CRC compared to COPD; median(IQR) urge to cough scores: 3 (2–3) vs 2 (1–3) and eating and drinking scores: 2 (0–3) vs 1 (0–2) respectively, both p=0.02. Geometric mean(SD) C2 and C5 in COPD were 9.5 (18.2) and 10.9 (18.0) micromol.L -1 . There was a significant correlation between C5 and urge to cough in COPD (rs =−0.74, p=0.02) but not with sputum trigger score (rs =−0.10, p=0.80). Conclusion: Sputum is a significant self-reported trigger of cough in COPD. In contrast, urge to cough occurs more frequently in CRC. There are likely to be multiple mechanisms of cough in COPD and further studies should investigate whether phenotyping cough on the basis of self-reported triggers and somatic sensations can guide therapy.